Mapping of magnetic basement in Central India from aeromagnetic data for scaling geology - Kumar, Raj; Bansal, A.R.; Anand, S. P.; Rao, V. K.; Singh, Upendra K. (My University, 2017)
The Central Indian region has a complex geology covering the Godavari Graben, the Bastar Craton (including the Chhattisgarh Basin), the Eastern Ghat Mobile Belt, the Mahanadi Graben and some part of the Deccan Trap, the northern Singhbhum Orogen and the eastern Dharwar Craton. The region is well covered by reconnaissancescale aeromagnetic data, analysed for the estimation of basement and shallow anomalous magnetic sources depth using scaling spectral method. The shallow magnetic anomalies are found to vary from 1 to 3 km, whereas magnetic basement depth values are found to vary from 2 to 7 km. The shallowest basement depth of 2 km corresponds to the Kanker granites, a part of the Bastar Craton, whereas the deepest basement depth of 7 km is for the Godavari Basin and the southeastern part of the Eastern Ghat Mobile Belt near the Parvatipuram Bobbili fault. The estimated basement depth values correlate well with the values found from earlier geophysical studies. The earlier geophysical studies are limited to few tectonic units, whereas our estimation provides detailed magnetic basement mapping in the region. The magnetic basement and shallow depth values in the region indicate complex tectonic, heterogeneity, and intrusive bodies at different depths, which can be attributed to different thermo-tectonic processes since Precambrian.
Keywords: Aeromagnetic data; Magnetic basement; Central India; Fractals/scaling; Spectral method